2006
DOI: 10.1007/s10534-005-2997-2
|View full text |Cite
|
Sign up to set email alerts
|

Design of Iron chelators: Syntheses and iron (III) complexing abilities of tripodal tris-bidentate ligands

Abstract: The interest in synthetic siderophore mimics includes therapeutic applications (iron chelation therapy), the design of more effective agents to deliver Fe to plants and the development of new chemical tools in order to study iron metabolism and iron assimilation processes in living systems. The design of ligands needs a rational approach for the understanding of the metal ion complexing abilities. The octahedral arrangement of donor atoms is the most favourable geometry, allowing the maximum possible distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The observed spectral changes (small red shift in k max , slight decrease in molar absorptivity) and isosbestic points ( Fig. 5A and B) are consistent with spectral changes previously reported for catechol-to-salicylate iron chelation mode conversions [19,26,[39][40][41]. The third protonation (pK MH3L = 4.1; Fig.…”
Section: Iron(iii) Complex Formation and Protonation Constantssupporting
confidence: 90%
See 1 more Smart Citation
“…The observed spectral changes (small red shift in k max , slight decrease in molar absorptivity) and isosbestic points ( Fig. 5A and B) are consistent with spectral changes previously reported for catechol-to-salicylate iron chelation mode conversions [19,26,[39][40][41]. The third protonation (pK MH3L = 4.1; Fig.…”
Section: Iron(iii) Complex Formation and Protonation Constantssupporting
confidence: 90%
“…The pyoverdins are somewhat unique among naturally occurring siderophores in that they possess a combination of binding groups including a catecholate and a hydroxamate at the chain terminus, and either an additional hydroxamate or a hydroxycarboxylic acid in the middle of the chain [22,23]. The synthesis and characterization of several heterotripodal tris-bidentate siderophore mimics containing (i) two catecholates and one 8-hydroxyquionoline, (ii) two 8-hydroxyquinolines and one catechol, (iii) two hydroxypyridinones and one catecholate, and (iv) two 8-hydroxypyridinones and one 2-hydroxyisophtalamide, have been reported [24][25][26]. Here we present the synthesis, iron coordination properties, and biological activity of a novel heterotripodal, mono-hydroxamate, bis-catecholate siderophore mimic, N a ,-N e -bis[2,3-dihydroxybenzoyl]-L-lysyl-(c-N-methyl-N-hydroxyamido)-L-glutamic acid (H 6 L, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the diffusion of lipophilic FeQ could explain the higher tissue Fe 2+ concentration of test species despite their reduced root reductase activity in our FeQ systems. O‐Trensox is a synthetic chelator with three para‐ sulfonated 8HQ subunits that make it more hydrophilic (Baret et al ., 1995; d’Hardemare et al ., 2006). It has been reported to aid the Fe nutrition of dicotyledonous species (through extracellular chelate splitting as in Fe‐EDDHA, Strategy‐I) but not of Z. mays (as it lacks root‐reductase activity, Strategy‐II; Caris et al ., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…We reason that the primary difference in the types of phosphopeptides isolated comes from the inherent coordination variations between the two metals. It has been previously suggested that iron metal ions are typically bound in a heterocyclic chelation format [28, 29], while titanium is immobilized through bidentate bridging coordination [10, 30]. This has also been recently confirmed for the bioactive form of Ti(IV) [31].…”
Section: Resultsmentioning
confidence: 93%